Anti-Interleukin-6 Receptor Antibody Therapy-Induced Retinopathy in a Patient with Rheumatoid Arthritis. (24th December 2012) - Tada, Asumi; Hashida, Noriyasu; Tanaka, Toshio; Nishida, Kohji
Abstract : Tocilizumab, a humanized anti-human interleukin-6 (IL-6) receptor monoclonal antibody, is beneficial for treating autoimmune conditions such as rheumatoid arthritis (RA). The most common adverse event is upper respiratory tract infection; ocular side effects are rare. We describe a case of skin ulceration and bilateral retinopathy with multifocal cotton-wool spots and retinal hemorrhages in a patient with RA treated with tocilizumab. Tocilizumab administration increased the serum level of IL-6 without affecting the IL-8 levels. We could not exclude the possibility of blood coagulation or retinal vascular changes caused by tocilizumab. The current case highlights the need to consider that ocular adverse effects can develop in patients treated with tocilizumab.